Gaya Kepemimpinan Kepala Desa dalam Meningkatkan Kinerja Pelayanan Publik di Desa Sungai Kedukan - Aisyah Septia Putri; Doris Febriyanti; Amaliatulwalidain Amaliatulwalidain (Pencerah, 2022)
This study aims to analyze the Leadership Style of the Village Head, as the initial argument in this study, that village officials and village heads are the lowest community service base. This research is a type of qualitative research with research informants are the Village Head and Sungai Kedukan Apparatus, data collection using documentation, observation and in-depth interviews. The data analysis used consisted of data reduction, data presentation, and drawing conclusions. The results showed that the Village Head applied several approaches such as the Situational approach using the Hersey and Blanchard theory, namely Telling, Selling, Participating and Delegating, with this approach making it easier for leaders to improve performance in public services. With a leader, there are those who provide encouragement, input and guidance to subordinates or employees at work.